2020
DOI: 10.17263/jlls.712669
|View full text |Cite
|
Sign up to set email alerts
|

Using Kahoot as a skill improvement technique in pronunciation

Abstract: Pronunciation is one of the main problems in language teaching and learning and it gets little attention. Most of students underestimate the importance of pronunciation considering that pronunciation is less important than other aspects of language. Many researchers investigated the weakness of pronunciation among students in all stages. However, there is still a strong need to develop pronunciation of foreign language students. This study aims to investigate the effectiveness of using Kahoot application for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
1
20
0
1
Order By: Relevance
“…Since Kahoot was launched in 2013, numerous scholars have explored it in different contexts, for example, Taiwan (Chiang, 2020), Turkey (Bicen & Kocakoyun, 2018) and New Zealand (Licorish et al, 2018). Furthermore, researchers have targeted the application of Kahoot in teaching various languages such as German (Chumairok & Ardiyani, 2020) and Chinese (Liu & Wang, 2017), and different language skills like vocabulary (Hadijah, Pratolo & Rondiyah, 2020) and pronunciation (Yürük, 2020). Some have even gone further and done research on the use of Kahoot in training academic subjects, for example, microbiology (Mohan, Nambiar, & Arvindakshan, 2018).…”
Section: Previous Studies On Kahootmentioning
confidence: 99%
“…Since Kahoot was launched in 2013, numerous scholars have explored it in different contexts, for example, Taiwan (Chiang, 2020), Turkey (Bicen & Kocakoyun, 2018) and New Zealand (Licorish et al, 2018). Furthermore, researchers have targeted the application of Kahoot in teaching various languages such as German (Chumairok & Ardiyani, 2020) and Chinese (Liu & Wang, 2017), and different language skills like vocabulary (Hadijah, Pratolo & Rondiyah, 2020) and pronunciation (Yürük, 2020). Some have even gone further and done research on the use of Kahoot in training academic subjects, for example, microbiology (Mohan, Nambiar, & Arvindakshan, 2018).…”
Section: Previous Studies On Kahootmentioning
confidence: 99%
“…Kahoot! also offers an effective strategy in terms of providing a fun environment in English education (Putri, 2019;Yürük, 2020), improves Arabic language grammar knowledge and motivation (Eltahir, Alsalhi, Al-Qatawneh, AlQudah, & Jaradat, 2021), increases engagement (Budiati, 2017), and especially helps students in concept teaching (Medina &Hurtado, 2017;Plump & LaRosa, 2017). It benefits educators as well as students (Zengin, Bars, & Şimşek, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…has a positive effect on teachers' and students' attitudes and increases engagement (Wang & Tahir, 2020). Yürük (2020) found that Kahoot! positively affects students' EFL pronunciation skills.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The use of Kahoot! application could improve university students' EFL pronunciation skills at various learning stages in Turkey (Yürük, 2020).…”
Section: Academic Achievementsmentioning
confidence: 99%